Payroll Information System Effect on Teacher and Staff Satisfaction In Smk Wirasaba - Juwita Sari Sihombing; Rubiatna Hardja; Yeti Rafitasari (Institute of Computer Science (IOCS), 2022)
Information systems are developing in the current global era. It really needs human resources who can develop within one scope of a company. By changing the performance of employees, the influence on the compensation of a company is needed because it affects the level of employee satisfaction at work. This study aims to determine the effect of compensation and job satisfaction on employee performance at Wirasaba Vocational School by collecting data using descriptive and narrative methods with a quantitative approach and conducting observations by giving questionnaires to teachers and staff to support the theories needed in this journal. Suggestion which are given by adding employees in filling out questionnaires to increase data accuracy with the conclusion that there is a positive and significant influence between compensation variables on job satisfaction in performance. By providing additional facilities for teachers and staff to increase the level of job satisfaction and will have an impact on performance teachers and staff.